2020
DOI: 10.1002/joa3.12364
|View full text |Cite
|
Sign up to set email alerts
|

Application of the simple atrial fibrillation better care pathway for integrated care management in frail patients with atrial fibrillation: A nationwide cohort study

Abstract: Background The benefit of integrated care management was unknown in frail atrial fibrillation (AF) patients. This study evaluated whether compliance with the atrial fibrillation Better Care (ABC) pathway for integrated care management would improve clinical outcomes in frail AF patients. Methods From the Korea National Health Insurance Service database, 262,987 nonvalvular AF patients were enrolled between 1 January 2005 and 31 December 2015. For each patient, the Hospital Frailty Risk Score and category were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 24 publications
(36 reference statements)
3
50
0
Order By: Relevance
“…30 All the observational studies consistently reported an association with a significant reduction in the risk of cardiovascular events and all-cause death, ranging from 10% to 60% per cent reduction in risk according to the various cohorts studied, together with a reduction in the risk of hospitalization. [8][9][10][11][28][29][30] In a contemporary Europeanwide AF cohort, clinical management adherent to the ABC pathway was associated with a 40% to 50% reduction in the major clinical outcomes. 28 In the recent mAFA randomized clinical trial, ABC pathway use resulted in a 60% reduction in the composite outcome of thromboembolic events/rehospitalization/all-cause death over a 1 year follow-up.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…30 All the observational studies consistently reported an association with a significant reduction in the risk of cardiovascular events and all-cause death, ranging from 10% to 60% per cent reduction in risk according to the various cohorts studied, together with a reduction in the risk of hospitalization. [8][9][10][11][28][29][30] In a contemporary Europeanwide AF cohort, clinical management adherent to the ABC pathway was associated with a 40% to 50% reduction in the major clinical outcomes. 28 In the recent mAFA randomized clinical trial, ABC pathway use resulted in a 60% reduction in the composite outcome of thromboembolic events/rehospitalization/all-cause death over a 1 year follow-up.…”
Section: Discussionmentioning
confidence: 92%
“…Since its proposal, the ABC pathway has been evaluated in observational retrospective studies 8‐10,28,29 and one randomized controlled trial 13 . Also, ABC pathway adherent care was associated with a reduced risk of adverse events even in clinically complex AF patients (those with multimorbidity, polypharmacy and hospitalized ones), 11 as well as in those AF patients found to be frail 30 . All the observational studies consistently reported an association with a significant reduction in the risk of cardiovascular events and all‐cause death, ranging from 10% to 60% per cent reduction in risk according to the various cohorts studied, together with a reduction in the risk of hospitalization 8‐11,28‐30 .…”
Section: Discussionmentioning
confidence: 99%
“…After the titles and abstracts screening, 14 full texts were evaluated, and eight studies were included in the final systematic review and meta-analysis(16-23) (Table 1) [Figure S1], with a total of 285,253 AF patients included (23). Four studies were based in Europe (17,18,20,24), two in Asia (22,23), one in North America (19) and one was multinational (21).…”
Section: Resultsmentioning
confidence: 99%
“…Among the eight included studies, two were post-hoc subgroup analyses of previously performed RCTs (19,21), four were based on observational registries (16)(17)(18)20) while the last one was derived from a nationwide claims registry (22). One study did not include a follow-up phase (17).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation